STRATEGI PENDIDIKAN TJOKROAMINOTO DALAM RUMAH KOST SOEHARSIKIN SURABAYA (1912-1922) - Rintahani Johan Pradana (Jurnal Sejarah dan Budaya, 2014)
Abstrak. Pendidikan dapat dipahami dalam bentuk pendidikan formal, pendidikan non-formal ataupun pendidikan informal. Keluarga sebagai pendidikan non formal memiliki peran yang besar dalam menanamkan nilai-nilai pendidikan bagi generasi masa depan. Tjokroaminoto dapat menjadi teladan bagi pengembangan strategi pendidikan non-formal. Dia mengubah rumahnya menjadi rumah kos. Tjokroaminoto menerapkan strategi pendidikannya bagi anak kos kemudian mempengaruhi pemikiran dan pergerakan muridnya. Abstract: Education can be a form of formal education, non-formal education or informal education. The family as a non-formal education has a great role to provide educational values the next generation. Tjokroaminoto could be an example of the non-formal education strategies. He changes his home into a boarding house. Tjokroaminoto applies his educational strategies for his student (“anak kos as a student) then influencing the students’ thought and movement.